Interfacial Interaction between Zn2+ and Surface Functional Groups Impacting Self-Assembly of ZnO on Cellulose Nanofibrils - Zhang, Lili (Langmuir : the ACS journal of surfaces and colloids, 2024)
The mechanism underlying the interfacial interaction between ZnO and surface functional groups, which drives the self-assembly of ZnO nanoflowers on the cellulose nanofibril (CNF) surface, remains inadequately understood. Moreover, the ideal sites for the loading and growth of ZnO nanoflowers on the oxygen atoms (Os) of various surface functional groups on the CNF surface are not well-defined. This work addressed these gaps by systematically regulating the size and surface charge density of CNF templates through minor surface modifications and adjustments in processing cycles by using an ultrafine grinder. Physicochemical analyses demonstrated that the ZnO nanoflowers exhibited sizes (μm)/pieces/thickness (nm) of 0.86/16/20.1 for ZnO/TOCNFs, 0.88/17/20.4 for ZnO/ACNFs, and 0.89/16/20.5 for ZnO/ECNFs, respectively. Simulation calculations revealed that the interaction between Zn2+ ions and the Os of hydroxyl (-OH) groups exhibited the most favorable binding energy of -31.7 kcal/mol. These findings suggested that the surface charge density rather than specific surface functional groups primarily governs the loading and growth of ZnO nanoflowers on the CNF surface. The OS from -OH groups on the surface of CNF templates were optimal for both the loading and growth of ZnO nanoflowers. Overall, this study provides crucial theoretical insights into the design and optimization of the ZnO/CNF composites